Factors causing yield gap in rape seed production in the eastern of Mazandaran province, Iran - Nezamzade, Esmail; Soltani, Afshin; Dastan, Salman; Ajamnoroozi, Hossein (Italian Journal of Agronomy, 2020)
The reduction of yield gap and achievement yield potential of oil plants make a significant contribution to yield increases and oil production in developing countries. This research was carried out to investigate the factors causing yield gap associated with rape seed crop management in the Neka region, east of the Mazandaran province, Iran, through a field study during 2015-2016 and 2016- 2017. Boundary line analysis (BLA) was only applied to crop management practices/inputs, e.g. sowing date and rate, fertilizer applications, etc. Boundary lines were fitted to the edge of the data cloud of crop yield versus management variables in data. The average yield in 100 farms was 2051 kg/ha. According to findings of BLA, an average yield, based on the optimum level of the 14 studied variables, was 3032 kg/ha with a 981 kg/ha yield gap per hectare. The average relative yield and relative yield gap for the 14 investigated variables were 68.35% and 31.65%, respectively. Therefore, it can be concluded that the use of the boundary line analysis in yield gap studies can clearly show the yield responses to management factors and calculate the possible potentials. Thus, cultivation practice management of the studied variables in farmers’ fields can lead to increased yield and reduced yield gap.